Social accounting matrix and the system of national accounts: an application - Santos, Susana (2009)
The purpose of this session is to show how the System of National Accounts (SNA) and the input-output (supply and use) tables are used to construct a Social Accounting Matrix (SAM). Based on the country's National Accounts, an aggregate SAM will be constructed for the Portuguese economy and their full consonance will be demonstrated by identifying both the items and balances of the various internal accounts of the System in the constructed SAM. The SAM will be shown as a working instrument for quantifying the flows in the economic circuit, and blocks of sub-matrices with common characteristics will be described in terms of the accounting transactions that are included in each of them. As an example, a more detailed SAM will be constructed and the contents of its cells described in strict detail. The relationship between the SAM and the input-output table will also be briefly analysed.